“Simple model of resource exploitation” - Reis, A. Heitor (2012)
Here we present a simple model of finite resource exploitation that is parameterized by initial cost ratio, a technologic and management index m accounting for the rise of the exploitation cost with decrease of resource amount, plus another index  accounting for the avidity of the market to the resource. The analysis showed that the model captures essential features of finite resource exploitation, namely those concerning to oil exploitation. Scenarios for future oil exploitation based on parameters estimated from historical data are analyzed and discussed, as well some other scenarios of generic resource exploitation.